Official Secrets Act 1972: looking at citizens' rights / Khazrin Haffiz Khalil, Mohd Asrulnizam Harun and Muhammad Fairuz Abdul Karim - Khalil, Khazrin Haffiz; Harun, Mohd Asrulnizam; Abdul Karim, Muhammad Fairuz (2007)
This research was conducted to determine the position of Malaysians* right to information under the Federal Constitution. This research also seeks to look at the constitutionality of Section 2B of the Official Secrets Act 1972 which allegedly erode the citizens' right to information. Finally, the issues of whether the Freedom of Information Act should be introduced in Malaysia will be discussed.